P430 TUMORAL THROMBOTIC MICROANGIOPATHY: A RARE CAUSE OF ACUTE PULMONARY HYPERTENSION. (18th May 2022) - D'Addazio, M; De Gaspari, M; Porcelli, G; Perazzolo Marra, M; Mancuso, D; Basso, C
Abstract: Introduction: Among the causes of acute pulmonary hypertension, the occlusion of the little pulmonary vessels caused by tumoral microemboli, even from an unknown neoplasm, is an infrequent condition with a very poor prognosis. Clinical Case: A 55–years old woman with no relevant past medical history presented to the Emergency Department with dyspnea at rest, desaturation, palpitations and a brief episode of chest pain, after several days of fatigue and exertional dyspnea. ECG showed sinus tachycardia and signs of right ventricle pressure overload with inverted T waves in V3–V4 and in the inferior leads (Fig. 1 ). On laboratory tests there were high D–dimer values and a slightly elevated TnI. Blood gas analysis showed hypoxemic hypocapnic respirstory alkalosis. An Echocardiogram revealed severe dilatation and dysfunction of the right ventricle and signs of high probability of pulmonary hypertension (Fig. 2 ). Pulmonary CT scan ruled out embolism and showed irregular thickening of the interstitium and mediastinal lymphoadenopathy. Then, a rapid clinical deterioration happened, refractory to inotropes infusion and larger volumes of oxygen. The programmed diagnostic pathway cannot be pursued. On day 4, there was respiratory distress and pulseless electrical activity cardiac arrest during endotracheal intubation. ECMO mechanical support was positioned but on day 7 the patient died. Autopsy, made to discover the cause of pulmonary hypertension, revealed the presence of a colonic invasive adenocarcinoma with micropapillary pattern and thoracic and pelvic lymph–nodal metastases. Microscopic evaluation of the lungs showed a widespread neoplastic vascular invasion with microthromboemboli (Fig. 3 ). Discussion: Tumoral thrombotic microangiopathy is a cause of pulmonary hypertension of multifactorial origin and should be suspected in cases of pulmonary hypertension without pulmonary embolism or interstitial lung disease. The rarity of this condition and the absence of an oncological medical history make difficult the diagnostic hypothesis. Besides, the lacking of an effective therapy makes the prognosis poor.